2022
DOI: 10.1177/23743735221077546
|View full text |Cite
|
Sign up to set email alerts
|

Does Insurance Status Influence Outpatient Flow? Cross-Sectional Comparison of Insured and Uninsured Patients in a Tertiary Hospital in Nigeria

Abstract: Background: While patient satisfaction is a core index for the assessment of health quality, waiting time and payment mode in hospitals could influence outpatients’ flow and as well as their level of satisfaction. Objective: This study compared the waiting time of insured and uninsured patients seeking general outpatient care in a tertiary hospital. Methods: A total of 166 insured and 166 uninsured ambulatory adult patients seeking outpatient services were recruited by systematic random sampling and followed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The results of this study were not consistent with some previous findings. The patients' waiting time in our study was shorter than that of insured patients in a tertiary hospital in Nigeria, as reported by Opurum et al [3]. They proposed that there were significant differences in mean total idle time during outpatient visits (65.7 min) and total time spent (106.6 min), and the results favored insured patients.…”
Section: Principal Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…The results of this study were not consistent with some previous findings. The patients' waiting time in our study was shorter than that of insured patients in a tertiary hospital in Nigeria, as reported by Opurum et al [3]. They proposed that there were significant differences in mean total idle time during outpatient visits (65.7 min) and total time spent (106.6 min), and the results favored insured patients.…”
Section: Principal Findingssupporting
confidence: 72%
“…The excessive waiting time in outpatient clinics is regarded as a major problem in health care management worldwide [1,2]. Hospital waiting time and payment methods influence outpatient flow and satisfaction [3]. Previous studies have reported that long waiting time for a medical consultation has become an important factor affecting outpatients' satisfaction [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Hanawi et al ventured into this uncharted territory, revealing a noteworthy correlation between insurance coverage and the promptness of medical treatments [4]. This revelation has highlighted the potentially pivotal role of insurance status in shaping the timely delivery of healthcare services [7]. Yet, despite these significant findings, the scholarly landscape continues to grapple with a palpable gap in comprehensive inquiry into the intricate interplay between physicians' perceptions and their navigation of the intricate disparities within the Saudi Arabian healthcare fabric.…”
Section: Introductionmentioning
confidence: 99%